Analysis of River Sediment Transport Way Sekampung (Upstream of Batutegi Dam) Using an Empirical Approach and HEC-RAS Modeling - Pradipta, Singgih; Purwadi, Ofik Taufik; Welly, Margaretta (Universitas Lampung, 2020)
Dams have various functions and benefits, such as irrigation sources, flood control, power generation, tourism etc. The problem that is concerned about the dams that have been built in developing countries such as Indonesia is in particular the problem of sedimentation in the reservoir. Way Sekampung is one of the rivers which is the source of water in the Batutegi reservoir. Way Sekampung has a large discharge. However, Way Sekampung which has a fairly heavy flow also carries sediment which must be taken into account so as not to disturb the stability of the existing river. Therefore, a research was conducted on sediment discharge and transport in the Way Sekampung river. The discharge analysis used field current meter data and sediment analysis used field sediment samples. Comparative data is calculated using the HEC-RAS application so that there are variations in the discharge in the calculation. The Way Sekampung River produces a sediment discharge of 0.0814 m3 / s at Cross Section 1 and 0.0999 m3 / s in Cross Section 2 using the Meyer Peter and Muller method. Compared with empirical calculations, the sediment rate value is 0.0822 m3 / s in Cross Section 1 and 0.0798 m3 / s in Cross Section 2 using HEC-RAS discharge modeling and Einstein method.